Upaya Guru Akidah Akhlak Mengurangi Adiksi Smartphone Melalui Layanan Bimbingan Klasikal dalam Pembelajaran PAI di MTsN 3 Magetan - Rasta Nugroho Saputra; Zamzam Mustofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This research analyzes the efforts of Akidah Akhlak teachers in reducing smartphone addiction through classical guidance services in Islamic religious education (PAI) learning at MTsN 3 Magetan. The method used was qualitative observational, with data obtained through interviews, observation, and documentation. The results show that classical guidance methods such as Team Game Tournament (TGT), Student Teams Achievement Division (STAD), and Jigsaw were effective in fostering student engagement and reducing smartphone use during class. Supporting factors include school regulations, teacher-parent collaboration, and interactive learning environments, though external environmental influences remain a challenge.